A Multielectrode Array-Based Recording System for Analyzing Ultrasound-Driven Neural Responses in Brain Slices in vitro - Furukawa, Ryo; Kaneta, Hiroki; Tateno, Takashi (Frontiers in Neuroscience, 2022)
Ultrasound stimulation is expected to be useful for transcranial local and deep stimulation of the brain, which is difficult to achieve using conventional electromagnetic stimulation methods. Previous ultrasound stimulation experiments have used various types of acute in vitro preparations, including hippocampus slices from rodents and Caenorhabditis elegans tissue. For in vivo preparations, researchers have used the cortices of rodents as targets for transcranial ultrasound stimulation. However, no previous studies have used in vitro ultrasound stimulation in rodent cortical slices to examine the mechanisms of ultrasound-driven central neural circuits. Here we demonstrate the optimal experimental conditions for an in vitro ultrasound stimulation system for measuring activity in brain slices using a multielectrode array substrate. We found that the peak amplitudes of the ultrasound-evoked cortical responses in the brain slices depend on the intensities and durations of the ultrasound stimulation parameters. Thus, our findings provide a new in vitro experimental setup that enables activation of a brain slice via ultrasound stimulation. Accordingly, our results indicate that choosing the appropriate ultrasound waveguide structure and stimulation parameters is important for producing the desired intensity distribution in a localized area within a brain slice. We expect that this experimental setup will facilitate future exploration of the mechanisms of ultrasound-driven neural activity.